(x+1)(x-2)+2x=(x-3)(x+2)

Simple and best practice solution for (x+1)(x-2)+2x=(x-3)(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)(x-2)+2x=(x-3)(x+2) equation:


Simplifying
(x + 1)(x + -2) + 2x = (x + -3)(x + 2)

Reorder the terms:
(1 + x)(x + -2) + 2x = (x + -3)(x + 2)

Reorder the terms:
(1 + x)(-2 + x) + 2x = (x + -3)(x + 2)

Multiply (1 + x) * (-2 + x)
(1(-2 + x) + x(-2 + x)) + 2x = (x + -3)(x + 2)
((-2 * 1 + x * 1) + x(-2 + x)) + 2x = (x + -3)(x + 2)
((-2 + 1x) + x(-2 + x)) + 2x = (x + -3)(x + 2)
(-2 + 1x + (-2 * x + x * x)) + 2x = (x + -3)(x + 2)
(-2 + 1x + (-2x + x2)) + 2x = (x + -3)(x + 2)

Combine like terms: 1x + -2x = -1x
(-2 + -1x + x2) + 2x = (x + -3)(x + 2)

Reorder the terms:
-2 + -1x + 2x + x2 = (x + -3)(x + 2)

Combine like terms: -1x + 2x = 1x
-2 + 1x + x2 = (x + -3)(x + 2)

Reorder the terms:
-2 + 1x + x2 = (-3 + x)(x + 2)

Reorder the terms:
-2 + 1x + x2 = (-3 + x)(2 + x)

Multiply (-3 + x) * (2 + x)
-2 + 1x + x2 = (-3(2 + x) + x(2 + x))
-2 + 1x + x2 = ((2 * -3 + x * -3) + x(2 + x))
-2 + 1x + x2 = ((-6 + -3x) + x(2 + x))
-2 + 1x + x2 = (-6 + -3x + (2 * x + x * x))
-2 + 1x + x2 = (-6 + -3x + (2x + x2))

Combine like terms: -3x + 2x = -1x
-2 + 1x + x2 = (-6 + -1x + x2)

Add '-1x2' to each side of the equation.
-2 + 1x + x2 + -1x2 = -6 + -1x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-2 + 1x + 0 = -6 + -1x + x2 + -1x2
-2 + 1x = -6 + -1x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-2 + 1x = -6 + -1x + 0
-2 + 1x = -6 + -1x

Solving
-2 + 1x = -6 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-2 + 1x + x = -6 + -1x + x

Combine like terms: 1x + x = 2x
-2 + 2x = -6 + -1x + x

Combine like terms: -1x + x = 0
-2 + 2x = -6 + 0
-2 + 2x = -6

Add '2' to each side of the equation.
-2 + 2 + 2x = -6 + 2

Combine like terms: -2 + 2 = 0
0 + 2x = -6 + 2
2x = -6 + 2

Combine like terms: -6 + 2 = -4
2x = -4

Divide each side by '2'.
x = -2

Simplifying
x = -2

See similar equations:

| -22=7x+22 | | 6x+8+6x=140 | | x^2+0.06x=0.028 | | 5[3x-2]=20 | | w-7=150 | | 4-8x+2=30 | | 7w=150 | | 64-12= | | 7-w=150 | | -10.95+12.48+18.6p=-17.97+16.1p | | -3r+3=-4r+5 | | 3+5y=30+2y | | 20x^4-65x^3-60x^2=0 | | -(1+7)-5(-7-x)=36 | | -8q+18q+10=7q-17 | | 65=6c+11 | | 3a-6(4a+5)=-6a-15 | | 2x-1=12x+121 | | 20z-14=5z+20z+11 | | 6=4+2z | | 6x^3+32x^2-10x=0 | | 2c-10+2=-20c-8 | | 118=1-3(6x-3) | | 19-17g=-8g-14g-6 | | 2p=-3 | | 7+2a=15 | | 19-17g=8g-14g-6 | | 2+4x=-4+x | | -12=4+4f | | 22+c=16 | | 10m-18-3=7+8m | | -(x-8)=x-38 |

Equations solver categories